Faktor-faktor Yang Mempengaruhi Kunjungan Wisatawan Pada Objek Wisata Air Terjun Tunan Di Desa Talawaan Kecamatan Talawaan Kabupaten Minahasa Utara - Rengkung, Regina Ceali; Kapantow, Gene Henfried Meyer; Tarore, Melissa Lady Gisela (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This study aims to determine the factors that influence tourist visits to the Tunan Waterfall tourist attraction in Talawaan Village, Talawaan District, North Minahasa Regency. The research method used is quantitative method, which uses Multiple Linear Regression analysis method, with Accidental Sampling technique. The instrument used in this research is a questionnaire. From the t test conducted, it was found that two variables had a significant effect on tourist visits to the Tunan Waterfall tourist attraction, namely the attractiveness variable (X1), service (X4) and there were two variables that had no significant effect on tourist visits to the Tunan Waterfall tourist attraction, namely facilities (X2), accessibility (X3). From the results of the F test it is proven that the variables of attractiveness (X1), facilities (X2), accessibility (X3), service (X4) together have a significant effect on tourist visits to the Tunan Waterfall tourist attraction. The coefficient of determination is 28%, while the remaining 72% is influenced by other variables not discussed in this study such as weather factors, cost factors, promotional factors and others.